Plastics engineering - Crawford, R. J. 1949- (Butterworth-Heinemann, 1998)
In this third edition over half the book has been re-written and the remainder has been updated and re-organized. Early chapters give an introduction to types of plastics available and describe how a designer goes about the selection of a plastic for a particular application. Later chapters lead the reader into more advanced aspects of mechanical design and analysis of polymer melt flow. All techniques developed are illustrated by worked examples, and problems are given at the end of each chapter; solutions to which form one of the appendice.
Keywords: Plastics.; elektronické knihy; electronic books